2017
DOI: 10.11114/jets.v5i9.2476
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Educational Policies for School-aged Syrian Refugees in Turkey

Abstract: The purpose of this study is to analyse the educational policies for Syrian school-aged refugees in Turkey. In this study, we identified the policy priorities for refugees by first examining the theoretical approaches to refugee education and the common problems observed for refugee education in different countries. Using this framework, we assessed refugee students' access to education and the studies on providing quality education to school-aged refugees through an examination of the relevant legislation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 4 publications
0
14
0
3
Order By: Relevance
“…However, several relevant studies indicated that both Syrian students and other CLD students often experience such problems as exclusion, loneliness, prejudices, discrimination, academic failures in Turkish public schools (Kotluk, 2018;Kotluk & Kocakaya, 2018b). This means that teachersí skills in teaching CLD students in Turkey remains one of the important problems (Alpaydin, 2017). In Kotlukís (2018) doctoral dissertation, he revealed that teachers had challenges that related to culturally different parents and students, and teaching CLD students.…”
Section: Discussionmentioning
confidence: 99%
“…However, several relevant studies indicated that both Syrian students and other CLD students often experience such problems as exclusion, loneliness, prejudices, discrimination, academic failures in Turkish public schools (Kotluk, 2018;Kotluk & Kocakaya, 2018b). This means that teachersí skills in teaching CLD students in Turkey remains one of the important problems (Alpaydin, 2017). In Kotlukís (2018) doctoral dissertation, he revealed that teachers had challenges that related to culturally different parents and students, and teaching CLD students.…”
Section: Discussionmentioning
confidence: 99%
“…Much research also indicated that integration of Syrian refugee students into main education system is very much vital and required (Aydın et al, 2019;Bircan & Sunata, 2015). To this end, government created different educational opportunities for these students in a dual system both for students living in the camps and living out of camps (Alpaydin, 2017). Many educational structures such as public schools, camp education centers, temporary education centers (Taşkin & Erdemli, 2018) and many other local initiatives such as informal schools where Syrian teachers willingly teach (Bircan & Sunata, 2015) were created to give large body of opportunities to these students.…”
Section: Refugees and Education In Turkeymentioning
confidence: 99%
“…On the other hand, under prospective or urgent action-based educational policies, education can serve as a compensatory tool for refugees by reducing uncertainty and increasing self esteem. Aside that, community support, teacher qualifications, educational tools and management structure can systemically affect refugees' educational attainments (Alpaydın, 2017). It is important to note that the education provided to refugees should be high quality and have meaningful value for them, otherwise the desired attainments will not be achieved (Dryden-Peterson, 2011).…”
Section: Introductionmentioning
confidence: 99%